Draft genome sequence of Kei apple, an underutilized African tree crop - Kariba, R.; Waweru, Bernice; Njaci, Isaac; Banda, L.; Mwangi, J.W.; Harimanantsoa, A.; Muthemba, S.; Featherstone, J.; Hendre, P.; Jamnadass, Ramni H.; Van Deynze, A.; Domelevo Entfellner, Jean-Baka; et al. (Nature Research, 2025)
To address food and nutrition security in the face of burgeoning global populations and erratic climatic conditions there is a need to include nutrient dense, climatic resilient but neglected indigenous fruit trees in agrifood systems. Here we present the draft genome sequence of Kei Apple, Dovyalis afra, a neglected indigenous African fruit tree with untapped potential to contribute to nutrient security and improved livelihoods. Our long-read-based genome assembly comprises 440 Mbp sequence across 1190 contigs with a N50 and L50 of 13.3 Mbp and 11, respectively. We also annotated the genome and identified 27,449 protein-coding genes. Our genome assembly provides a valuable resource for unlocking the food security and nutraceutical potential of Kei apple.